2-Trifluoromethyl-6-mercurianiline Nucleotide, a Sensitive F-19 NMR Probe for Hg(II)-mediated Base Pairing - Aro-Heinilä Asmo; Lepistö Assi; Äärelä Antti; Lönnberg Tuomas Antti; Virta Pasi (AMER CHEMICAL SOC, 2022)
A 2-trifluoromethylaniline C-nucleoside was synthesized, incorporated in the middle of an oligonucleotide, and mercurated. The affinity of the mercurated oligonucleotide toward complementary strands placing each of the canonical nucleobases opposite to the organomercury nucleobase analogue was examined by ultraviolet (UV), circular dichroism (CD), and F-19 NMR spectroscopy analyses. According to the UV melting profile analysis, the organomercury nucleobase analogue showed increased affinities in the order T > G > C > A. The CD profiles indicated the typical B-type helix in each case. The F-19 resonance signal proved sensitive for the local environmental changes, showing clearly distinct signals for the duplexes with different opposing nucleobases. Furthermore, valuable information on the mercurated oligonucleotide and its binding to complementary strands at varying temperature could be obtained by F-19 NMR spectroscopy.